Türk Kardiyoloji Dernegi Uzlaşi Raporu: COVID-19 Pandemisi ve Kardiyovasküler Hastaliklar Konusunda Bilinmesi Gerekenler (13 Mayis 2020) - Aktoz, Meryem; Altay, Hakan; Aslanger, Emre; Atalar, Enver; Atar, Ilyas; Aytekin, Vedat; Yildizeli, Bedrettin (Turkish Society of Cardiology, 2020)
[Abstract Not Available]
Keywords: Betacoronavirus; Cardiology; Cardiovascular Diseases; Consensus; Coronavirus Infections; Humans; Pandemics; Pneumonia, Viral; Practice Guidelines as Topic; Betacoronavirus; cardiology; cardiovascular disease; complication; consensus; coronavirus disease 2019; Coronavirus infection; human; pandemic; practice guideline; virus pneumonia